TUMPANG TINDIH PENGUASAAN TANAH DI WILAYAH IBU KOTA NEGARA “NUSANTARA” - Rikardo Simarmata (Faculty of Law, Parahyangan Catholic University, 2023)
In August 2019, the Central Government of Indonesia made an important decision to choose East Kalimantan province to be the location of the new state capital (Nusantara). East Kalimantan was chosen due to its large available state or government-owned land. Some of the large available lands are designated state forest while some others are unregistered land, for which the Government applies formal land tenure system. This article examines the extent to which formal land tenure system has been exercised in land control, land transaction, and land acquisition in the Nusantara through the inquiries on how local individual and group landowners responded to the application of the formal land tenure system. Data collection was conducted through library research and field interview. This research finds that there have been multiple overlapping claims over land rights taking place in the new capital. State, adat law communities, and sultanate are making claims to similar land plots. The overlapping claims arose after the bureaucrats developed a formalistic view or interpretation on state land. This view suggested any unregistered land is state land regardless of actual control and use that are existing. This form of interpretation will most probably influence the way the bureaucrat implements current regulations concerning the new capital where some stipulations respect customary land rights.